KARAKTERISTIK BIODIESEL DARI MINYAK JELANTAH MENGGUNAKAN KATALIS ABU TANDAN KOSONG SAWIT - Budi Ariyani, Sukma; Asmawit; Hidayati (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2016)
The purpose of this study was to know the effect of adding a catalyst ash of palm empty fruit bunches on the number and characteristics of biodiesel produced from used cooking oil. The independent variables studied are heavy ash of palm empty fruit bunches (8, 10 and 12 g), the mole ratio of methanol: oil (6: 1, 9: 1 and 12: 1) and reaction time (60, 90 and 120 minutes). The results obtained are highest biodiesel yield is obtained of 54.7 mg/Kg on a reaction time of 60 minutes, the mole ratio of methanol:oil at 12:1, catalyst ash 10 g per 75 mL of methanol at a temperature of 60oC and stirring speed 600 rpm. Characteristics of biodiesel were analyzed in the study include the density, kinematic viscosity, cetane number, flash point, the point of fog, carbon residue, distillation temperature 90% vol, phosphorus, acid number and calorific value.